From Conviction to Candidacy: A Juridical and Siyasah Analysis of the Waiting Period for Former Corruptors under the Election Law - Utami, Husni Putri; Antasari, RR. Rina; Yusnita, Eti (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
The problem in this study departs from the KPU in its PKPU authorizing regulations regarding the pause period for ex-convicts not having to wait five years in the elections held in 2024. So that it produces two problem formulations, namely: 1) How is the Political Right to the Pause Period for Ex-Corruption Prisoners to Participate in Legislative Candidacy in the Perspective of Law (UU) Number 07 of 2017 concerning General Elections (Election) and General Election Commission Regulations (PKPU) Number 10 and 11 of 2023?, and 2) How is the Political Rights of Ex-Corruption Convicts to Participate in Legislative Candidacy in Siyasah Perspective? The research methodology used by the author is a type of normative law research, with a research approach using legal issues with the method of statue approach, case approach, and analytical approach. Based on the results of the author's research, it can be concluded that: 1) The Election Law, which is strengthened by the latest Constitutional Court Decision in 2023, explains that there is a pause period for ex-corruption convicts who want to run for the legislature to wait five years. Meanwhile, the PKPU 2023 does not. So that PKPU 2023 and the Election Law overlap, if PKPU 2023 was born to improve the Law as well as the Constitutional Court Decision, it should be in line. Regarding the hierarchy of legislation, PKPU is also under the Law, and this disharmonization occurs which is contrary to the coherent principles, one of which is certainty and harmony in regulations, and 2) That in Siyasah Dusturiyah it is explained that ex-corruption convicts are people who used to commit criminal acts, in Islam this person is considered a person who has a moral defect so that his rights cannot be fully obtained anymore, unless he really repents not only said but also implements through actions, of course with full self-awareness again of what has been done, it should be able to provide opportunities for others who still have integrity, because Islam recommends that it is better to choose and be chosen, namely choose the best people. [Permasalahan dalam penelitian ini berangkat dari KPU di PKPU-nya mengesahkan peraturan tentang masa jeda eks-narapidana tidak harus menunggu lima tahun pada Pemilu yang diselenggarakan tahun 2024 lalu. Sehingga menghasilkan dua rumusan masalah yaitu: 1) Bagaimanakah Hak Politik Terhadap Masa Jeda Pada Eks-Narapidana Korupsi Mengikuti Pencalonan Legislatif Perspektif Undang-undang (UU) Nomor 07 Tahun 2017 Tentang Pemilihan Umum (Pemilu) dan Peraturan Komisi Pemilihan Umum (PKPU) Nomor 10 dan 11 Tahun 2023?, dan 2) Bagaimanakah Hak Politik Pada Eks-Narapidana Korupsi Mengikuti Pencalonan Legislatif Perspektif Siyasah?. Metodelogi penelitian yang dipergunakan penulis adalah berjenis normative law research, dengan pendekatan penelitian menggunakan legal issue dengan metode statue approach, case approach, dan analytical approach. Berdasarkan hasil penelitian penulis dapat disimpulkan, bahwasanya: 1) Bahwa pada UU Pemilu yang dikuatkan oleh amar Putusan MK tahun 2023 terbaru dijelaskan terdapat masa jeda eks-narapidana korupsi yang hendak akan mencalonkan diri menjadi anggota legislatif harus menunggu lima tahun. Sedangkan PKPU Tahun 2023 tidak. Sehingga PKPU 2023 dan UU Pemilu terjadi tumpang tindih, semestinya apabila PKPU 2023 lahir untuk penyempurnaan dari UU juga Putusan MK seharusnya sejalan. Terkait hierarki perundang-undangan pun PKPU ini berada dibawah UU, dan ini terjadi disharmonisasi yang berlawanan dengan asas koheren salah satunya kepastian dan keselerasan dalam peraturan, dan 2) Bahwa dalam Siyasah Dusturiyah dijelaskan eks-narapidana korupsi ini adalah orang yang dulunya berbuat tindakan kriminal, dalam Islam orang ini dianggap orang yang telah cacat moral sehingga hak-haknya tidak bisa diperoleh penuh lagi, kecuali benar-benar bertaubat tidak hanya diucapkan saja namun juga mengimplementasikan lewat perbuatan, tentunya dengan penuh kesadaran diri lagi terhadap apa yang sudah diperbuat, seyogyanya bisa memberikan kesempatan kepada orang lain yang masih berintegritas, karena Islam mengajurkan sebaiknya untuk memilih maupun dipilih yaitu pilihlah orang-orang yang terbaik.]